Gambaran Deskriptif Usaha Modern Donat J.Co Dengan Usaha Tradisional Donat Madu - Dini Saffaanatul Fitri; Nathalia Angela; Eka Andriani (Jurnal Ilmiah Wahana Pendidikan, 2022)
J.CO Donuts is one example of a local franchise that has managed to survive in the restaurant business competition in Indonesia, especially in the donut sector, which is located on Jl. Ahmad Yani Boulevard, Bekasi. Donat Madu Cihanjuang (DMC) is a franchise company engaged in the snack food sector which was established in 2010 located on Jl. Cihanjuang Cimahi, West Java. The location of the honey donut business observed is located at Jl. Pemuda, Bekasi. The purpose of this analysis is to find out the difference between modern business management at Donat J.CO and traditional business at Donat Madu. The research design was carried out by means of descriptive analysis. The analysis was carried out in Bekasi on December 15, 2020. It can be seen that the j.co donut business logo has the meaning of beauty, elegance, softness and immortality and the honey donut business logo has the meaning that this donut is related to honey. It can be seen that J.co Donuts has a competitor, namely Dunkin Donuts, while Honey Donuts has a competitor, namely Dino Donuts. The packaging for J.co Donuts and Honey Donuts uses food packaging in the form of a box made of disposable paper with the company logo on it. Consumer ratings of the modern food business Donat J.co are 4 while the traditional food business Donat Madu is 3. This shows that Donat J.co has a higher rating value than Donut Madu